Assessing the Conformity of Plasticizer-Free Polymers for Foodstuff Packaging Using Solid Phase Microextraction Coupled to Gas Chromatography/Mass Spectrometry - Nicoletta De Vietro; Antonella Maria Aresta; Jennifer Gubitosa; Vito Rizzi; Carlo Zambonin (Separations, 2024)
Phthalates are the synthetic chemical plasticizers with the most varied uses and are a source of concern due to their toxicity and ubiquity, so much so that even plasticizer-free polymers can contain them as non-intentionally added substances (NIAS). Food packaging is among the materials with the greatest impact. In this study, a simple protocol is proposed for the location and identification of dimethyl phthalate, diethyl phthalate, dipropyl phthalate, and dibutyl phthalate which is applicable to compliance studies of food packaging materials and for the associated risk assessment. Solid phase microextraction gas chromatography/mass spectrometry was used to evaluate the migration of four NIAS from food packaging to release media simulating food substrates. Three plasticizer-free polymers were used: two that were lab-made and based on sodium alginate and a commercial polyethylene film. Linearity ranged from the LOQ to 10 µg/mL; within-day and between-day precision values were between 12.3–25.7% and 21.9–35.8%, respectively; the LOD and LOQ were in the range 0.029–0.073 µg/mL and 0.122–0.970 µg/mL. Migration tests were conducted for different periods of time at room temperature and at 8 °C. Exposure to microwaves (MW) was also evaluated. All packaging materials tested had global migration limits lower than 10 mg/dm2 of material surface.